Peatland Contribution to Stream Organic Carbon Exports From a Montane Watershed. Issue 11 (19th November 2019) - Rosset, T.; Gandois, L.; Le Roux, G.; Teisserenc, R.; Durantez Jimenez, P.; Camboulive, T.; Binet, S.
Abstract: Mountains contain many small and fragmented peatlands within watersheds. As they are difficult to monitor, their role in the water and carbon cycle is often disregarded. This study aims to assess the stream organic carbon exports from a montane peatland and characterizes its contribution to the water chemistry in a headstream watershed. High frequency in situ monitoring of turbidity and fDOM were used to quantify respectively particulate organic carbon (POC) and dissolved organic carbon (DOC) exports at the inlet and outlet of a peatland over three years in a French Pyrenean watershed (1, 343 m.a.s.l.). The DOC and POC signals are both highly dynamic, characterized by numerous short peaks lasting from a few hours to a few days. Forty‐six percent of the exports occurred during 9% of the time corresponding to the highest flows monitored at the outlet. Despite its small area (3%) within the watershed, the peatland contributes at least 63% of the DOC export at the outlet. The specific DOC flux ranges from 16.1 ± 0.4 to 34.6 ± 1.5 g m 2 year −1 . POC contributes 17% of the total stream organic carbon exports from the watershed. As the frequency of extreme climatic events is expected to increase in the context of climate change, further studies should be conducted to understand the evolution of underestimated mountainous peatland carbon fluxes and their implication in the carbon cycle of headwaters. Plain Language Summary: Since the last glacial period, peatlands have accumulated large stocks of organic carbon. Despite representing only 3% of global continental surfaces, they store about 22% of the continental soil carbon stock. In the context of global change, peatland carbon sequestration capacity needs to be carefully monitored. In addition to greenhouse gas exchanges with the atmosphere, determining this capacity requires the quantification of aquatic organic carbon exports. Aquatic organic carbon exports have rarely been investigated at mountainous peatlands. Moreover, global change is expected to drastically modify mountain hydrology, influencing aquatic carbon exports and carbon balance of mountainous peatlands. Using high frequency in situ instrumentation, this study shows the annual quantity of aquatic organic carbon exported from a montane peatland in the French Pyrenees is in the same range as Northern lowland peatlands. These highly variable exports mainly occur during high discharge events due to snowmelt or rainfalls. Despite its restricted area, this montane peatland is the main contributor of aquatic organic carbon in the watershed. Peatlands influence headwater chemistry and further study must be conducted to monitor the evolution of these mountainous carbon stocks. Key Points: High‐frequency monitoring revealed that 46% ± 3% of the stream organic carbon exports occurs during high discharge events (9% of time) A small peatland area (3%) contributes at least 63% of the stream organic carbon exports from a mountainous watershed DOC specific flux from the studied montane peatland ranges from 16.1 ± 0.4 to 34.6 ± 1.5 g C m −2 year −1